Experimental Study of Square CFST Stub Columns With a Low Steel Ratio Under Axial Loading - Lu, Deren; Gong, Yongzhi; Ding, Faxing; Wang, Liping; Deng, Chao; Yuan, Tao; Luo, Chen; Ren, Enhui (Frontiers in Materials, 2021)
This paper presents an experimental and numerical study on large dimension concrete-filled square low steel ratio steel tubular (CFST) stub columns under axial loading. Four specimens were designed to investigate the effects of steel ratio on the confinement effect of square CFST stub columns with a low steel ratio. ABAQUS was used to establish 3D finite element (FE) models for simulation of square CFST stub columns with a low steel ratio under axial loading. Furthermore, based on the experimental verification, the definition of the confinement index (ϕ = fsAs/(fcAc)) was discussed and the effect of the grade of concrete and steel tube was also investigated. With the same cross-sectional dimensions, the confinement effect of the square CFST stub columns with a low steel ratio (less than 0.05) was better than the others. The stub columns with the yield strength of steel tube fs = 235 MPa (345, 420 MPa) and compressive cubic strength of concrete fcu = 40 MPa (60, 80 MPa) can give fully demonstrate the material performance and reflect the better confinement effect. Based on the experimental results and FE modeling, a practical calculation formula for the ultimate load-carrying capacity of square CFST stub columns with a low steel ratio was proposed. The formula calculation results presented in this paper show good agreement with the experimental results. Compared with the existing formulas, the proposed formula has better precision.